Efficacy of Individualized Homeopathic Medicinal Products in LM Potencies in Cancer-Related Fatigue: Protocol for a Series of N-of-1 Trials, with Meta-analysis of Individual Patient Data - Ghosh, Shubhamoy; Siddique, Mahejabeen; Chatterjee, Koushik; Pal, Rajat K.; Alam, Sk Monsur; Halder, Indrani; Chandra, Suman; Midya, Ayan; Saha, Subhranil (Homeopathy, 2025)
Cancer-related fatigue (CRF) poses a significant challenge in cancer care and affects the quality of life of many patients. Despite the prevalence and impact of the condition, identifying effective therapies remains a challenge. Non-pharmacological remedies, such as complementary therapies including homeopathy, are under-researched. A clinical trial with n-of-1 design has therefore been planned to evaluate the potential of individualized homeopathic medicinal products (IHMPs) in the management of CRF.A series of double-blind, randomized, placebo-controlled, n-of-1 trials will be conducted. Each participant will undergo three rounds of two intervention phases in a randomly determined order. The study will be performed at the Oncology Outpatient Department of D. N. De Homoeopathic Medical College and Hospital. Participants with CRF who meet pre-defined eligibility requirements will be enrolled. The FACIT-F sub-scale is the primary outcome measure; Short Form-36 and the Wu Cancer Fatigue Scale are the secondary outcomes. All outcomes will be measured at baseline, on day 7 and then every 10 days for 2 months. The sample size will be the number of patients who can be recruited during the 18-month period of the trial. The Numerical Rating Scale (0–10) measuring fatigue severity will be used in screening and preliminary evaluation of the degree of fatigue. Comprehensive blood tests to evaluate various physiological factors related to CRF will also be performed. An assessment of the effect of the IHMPs will be obtained per individual and by aggregating the data of all participants via meta-analysis.The results of our study will clarify the possible therapeutic effects of IHMPs for patients with CRF, as well as improve our understanding of the n-of-1 study design as it is applied to homeopathy research.Clinical Trials Registry—India: CTRI/2024/03/064438.
Keywords: cancer; fatigue; homeopathy; placebo; n-of-1 trial